Pengaruh Biaya Produksi dan Harga Jual Terhadap Pendapatan Petani Pinang di Desa Lagan Tengah Kec. Geragai Kab.Tanjung Jabung Timur - Faridatul A’la; Titin Agustin Nengsih; Victor Diwantara (CV. Aksara Global Akademia, 2026)
This research is motivated by the fluctuation in income of areca nut farmers in Lagan Tengah Village, Geragai District, East Tanjung Jabung Regency, which has decreased in recent years. This condition is suspected to be caused by high production costs and unstable areca nut selling prices at the farm level. Therefore, this study aims to determine the effect of production costs and selling prices on areca nut farmer income in Lagan Tengah Village. This research used a quantitative approach with multiple linear regression analysis. The study population was all 1,105 areca nut farmers in Lagan Tengah Village, while the sample size was 92 people, selected using simple random sampling based on the Slovin formula with a 10% margin of error. Data were collected through questionnaires, interviews, observations, and documentation. Data analysis was performed using the classical assumption test, the t-test (partial), the F-test (simultaneous), and the coefficient of determination (R²) test. The results showed that production costs had a partial and significant negative effect on areca nut farmer income, while selling prices had a positive and significant effect on areca nut farmer income. Simultaneously, both variables—production costs and selling prices—have a significant impact on the income of areca nut farmers in Lagan Tengah Village. The coefficient of determination (R²) indicates that production costs and selling prices are able to explain variations in areca nut farmer income quite strongly. From these results, it can be concluded that improving production cost efficiency and stabilizing areca nut selling prices are important factors in increasing the income of areca nut farmers in Lagan Tengah Village. The local government and related institutions are expected to support farmers through subsidy policies, increased market access, and fostering farm management to optimize and sustain farmer income.